Irrigation System without Electricity - PHIEWKHAMPHOM , Sisaket (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
Drip Irrigation system without electricity has functioned pump water from low to high. to the purpose of this study was: to test the ability to absorb water in 5 minutes, 10 minutes and 15 minutes in order to conduct a test the efficiency of the drip irrigation system, save the electricity in the household and apply water to the community. The target site of applying this non-electric drip irrigation system is a biological garden at Luangprabang Teacher Training College and would be tested in a community where there in no electricity. From testing drip irrigation system, it can be found that: The test results show that a height of 80 cm-water pipe, the hose can pump up to 40 liters in 5 minutes, in 10 minutes, 90.2 liters of water can be pumped and in 15 minutes, 130.6 liters of water can be pumped. The more time we spend the more water we can absorb. Water pump made of plastic pipe which sized 30 at a height of 80 cm in 5 minutes can pump 40 liters of water, pumping efficiency was 56%, which in 10 minutes it can pump water at 90.2 liters, pumping efficiency is 61% and in 15 minutes can pump 130.6 liters, pumping efficiency is 61%.